MALE SEX HORMONES RESPONSE AFTER A MONTH LONG HIMALAYAS TREK IN RELATION TO HEMOGLOBIN OXYGEN SATURATION (Kinesiology, 2018)
High altitude tourism is becoming increasingly popular among non-athletic population but its potential impact on health is often neglected. This study investigated the changes in male sex hormones after the trek in altitudes between 1400m- and 6476m. 17 recreational lowland men (age 48±11) participated in 26 day Himalaya trek, with the highest point reached being Mera Peak. The initial measurements were performed 10 days before departure and included blood work (total testosterone, sex hormone-binding globulin (SHBG), dehydroepiandrosterone sulfate (DHEA-S), follicle stimulating hormone (FSH) and luteinizing hormone (LH)) and ergometry on treadmill. The final measurements were done 24h after return to 122m (4 days after altitude of 4300m, and 8 days after altitude of 6476m). During the tour SpO2 and heart rate were measured 21 times. An increase in SHBG (42.6±10.6 to 50.7±12.0 nmol·L-1; P=0.011), and subsequent decrease in calculated free testosterone (1.8±0.3 to 1.6±0.3%; P=0.003) were observed. There was a significant correlation between the relative testosterone decrease and SHBG with mean SpO2 (Spearman R=-0.64 and 0.41 respectively). LH and FSH increased significantly (FSH Median;IQR before= 3.9;0.42 and after 4.6;4.0-7.1 IU·L-1; P=0.001 and LH Median/IQR before= 4.8/3.1-5.2 and after 5.9/4.9-9.3 IU·L-1; P=0.008). The changes in LH and FSH did not correlate with SpO2 whereas physical fitness (expressed in MET) did. In conclusion, the pituitary-adrenal-gonadal axis was affected by altitude trek (involving physical exertion and hypoxia in combination) but the origin, duration and the impact of changes on various aspects of men’s health should be further investigated. Key words: altitude, gonadotropins, testosterone, hypoxia